Pneumonia in Camel in Iraq, II. Etiology - S. Mahmoud, Chyath; M. Mahmoud , Mahmoud,; M. Shakir, Mothana (The Iraqi Journal of Veterinary Medicine, 1990)
This study was carried out to investigate 87 lungs of camel slaughtered in Al-Najaf abattoir. These lungs were pneumonic and consolidated. Bactarial and parasitic isolation were applied on these lungs. lungs. Although 122 bacterial strain which belonged to 8 specles were isolated. The most common bacteria which isolated was E.coli Bacillus subtilis Staphlococcus epidermidis Staphlococcus aureus and Corynebactarium Pyogenes. While parasitic identification revealed the presence of hydatid cysts and certain lung worms similar to Dictyocaulus spices and a superficial nodules like that of Muellerius capillaris.